A filosofia do humanismo integral no direito: a contribuição do pensamento de Augusto Comte e Jacques Maritain para o fundamento jusfilosófico dos Direitos Humanos - Santiago, Bráulio Junqueira (2013)
Facing to my own concerns and this was one of the reasons to write this Thesis I am convinced that is not possible keeping thinking, acting and constructing juridical logical sctructures only trough formal basis. This period has already ended at Law Science and it didn t bring to us generous results. But if we know how to take advantage from its negative side, it will teach us a lot regarding the Law Science s reductionist vision, regardless its nature. Another innovative topic in this Thesis is about the consideration that the necessary demands of formal rationality and systemic consistency Comte under the knowledge of Law Science, precisely in dogmatic area, gathering to the growing complexity of social tensions and atavistic antagonisms to human beings Maritain. We are living in a normative crisis , which often doubts of state legitimacy in its jus-politics decisions. A crisis where the normative decisions are partly legitimate under the aspect of rules production and not of the legislating process, which starts in the beginning of the decision-making until the social efficiency. Ultimately, there are people who are able to find in Law Science not the dogmatic and autist reductionism, but a hope to view the Law as an independent organism perfectly able to think for itself. Besides, we are aware of, in the hodiernal world, it s hard to find anybody who submits to mourir pour les idées (die for an ideal). In the other hand, the scientific world so, Law including is open to the pluralism of ideas, using less absolute truth as premises. Today we know many lives hadn t been lost for nothing! For a truth that is not even useful anymore. I have noticed Science has realized that being humble can expand its research in the field or not so, it could give it more legitimacy in the scientific community. Therefore, I propose a reflection trough another view: considering the hierarchy and the formal aspect of latin Law Science combined with the flexibility and concerns regarding practicing Law to the Anglo-Saxon Law. In an innovative way, with the conciliate which for many apparently were irreconcilable of one of the most important leaders of Humanistic Law, Jacques Maritain, with a great philosopher, systematic organizer and humanity server, not to much reminded lately, Auguste Comte. The fact that I have conciliated ideas apparently irreconcilable, such as Maritain s and Comte s to guide this Scientific Paper, doesn t mean I underestimated all the jus-philosophical background of almost a decade of research. I used, indeed, even not so perceptible, the influences of my Masters for these ten years, as well the books read in the original language or translated about the issue